Discovery of insect Blaps rhynchopetera Fairmaire extracts with anti-tyrosinase activity and anti-melanin deposition - Zhang, Lamei; Cao, Kaixun; Yang, Xizhe; Zhou, Shengwen; Mwangi, James; Wang, Chengye; Chen, Yifan; Zhang, Chengchen; Wang, Ziyi; Zhao, Min; Shi, Lei; Lu, Qiumin (Frontiers in Pharmacology, 2025)
BackgroundBlaps rhynchopetera Fairmaire is a medicinal insect that has been used for a long time by minority ethnic groups in Yunnan, China, due to its immunomodulatory function. However, its potential applications in cosmetics have not been reported.MethodsIn vitro experiments were used to verify whether the extracts of B. rhynchopetera Fairmaire (EBR) have the effect of inhibiting TYR activity and eliminating melanin deposition. Subsequently, in vivo experiments were conducted to verify further the potential application of the EBR in whitening. To explore the whitening components of the EBR, we employed UHPLC-Q-TOF MS to identify the compounds present in the EBR and utilized network pharmacology to compare them with the genes involved in whitening in the database, thereby obtaining the intersection of compound targets and whitening targets. Then, protein-protein interaction network analysis, gene ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis were carried out to explore the main components of the whitening effect of the EBR. Further, molecular docking and molecular dynamics simulation were used to verify the correlation between the main components of the EBR and the essential target molecules.ResultsIn vitro and in vivo studies have found that the EBR exhibits anti-oxidation, TYR-inhibiting activity, and the elimination of melanin deposition. Subsequently, 1538 metabolites were identified by UHPLC-Q-TOF MS analysis, indicating that EBR is a rich source of bioactive compounds. Among them, 82 kinds of phenols and flavonoids may be derived from external enrichment or self-synthesis. Network pharmacology revealed 41 genes related to pigmentation and TYR inhibition. Molecular docking and molecular dynamics simulation confirmed that myricetin, luteolin, apigenin and quercetin have a high binding affinity with TYR, which may regulate melanin production by inhibiting TYR activity.ConclusionIn this study, we identified the primary whitening active ingredients of B. rhynchopetera Fairmaire and utilized network pharmacology and molecular dynamics simulation to investigate the mechanism underlying the whitening effect of EBR. This work reveals that insect extraction may have broad application prospects in the preparation of cosmetics. To our knowledge, this is the first report identifying the flavonoids quercetin, luteolin, myricetin, and apigenin as whitening-active components in insects.